If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(1x + 10) = -32 Reorder the terms: -4(10 + 1x) = -32 (10 * -4 + 1x * -4) = -32 (-40 + -4x) = -32 Solving -40 + -4x = -32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + -4x = -32 + 40 Combine like terms: -40 + 40 = 0 0 + -4x = -32 + 40 -4x = -32 + 40 Combine like terms: -32 + 40 = 8 -4x = 8 Divide each side by '-4'. x = -2 Simplifying x = -2
| 25+15=x | | .33(3x+6)=8x+10 | | -6=-5x+6 | | 9-2+5=260 | | 0.5(x+4)-(10x+9)=-65 | | -.5=4-4.5x | | 4x+(-3)=1 | | 11q=33 | | y=0.80(55)+136 | | 4x+(-3)=2 | | 8x-2=-9+7y | | .3(3x+6)=8x+10 | | 5(6+3x)=105 | | -5y+6=y+9 | | (-9-12)x=8-4x | | y=0.80(45)+136 | | 5x+-2x+5x=8 | | 20/(-4)=c | | x^2+x+30=0 | | .75x-1.25=-2 | | 64y^3-2=y-128y^2 | | 3h-15+h=5.2 | | y=0.80(35)+136 | | 3x-6=8(x-9) | | -10+3x=-2x+45 | | 8x-2=9+7y | | .20x+x=60 | | 3(x-1)-2=1/2(4x-8) | | (x+11)+(x+19)=16 | | y^2-36y-64=0 | | .6x+6.6=3.3 | | y^2-36y+64=0 |